2022
DOI: 10.52567/trj.v6i02.110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasound Therapy Versus Transverse Friction Massage Along With Eccentric Exercise Program on Chronic Achilles Tendinopathy

Abstract: Background: Achilles tendinopathy is highly prevalent and caused by intrinsic or extrinsic factors. The multiple minor traumas can lead to achilles tendinopathy. Physical therapy treatment includes soft tissue mobilization and exercises. Objective: To compare ultrasound and transverse friction massage in chronic Achilles tendinopathy. Methodology: The study was a randomized control trial from 1st March 2019 to 15th August 2019. The non-probability convenient sampling technique was used to include n=76 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Jumping activities were then added to this routine which progressed from double leg to single leg. The rehabilitation program also included 10 min of moist heat pack, application of pulsed ultrasound and deep transverse friction massage (34) of the patellar tendon for 5-10 min (Table 1) (35)(36)(37). The participants were advised to wear knee straps and modify activities (38).…”
Section: Conventional Physical Therapymentioning
confidence: 99%
“…Jumping activities were then added to this routine which progressed from double leg to single leg. The rehabilitation program also included 10 min of moist heat pack, application of pulsed ultrasound and deep transverse friction massage (34) of the patellar tendon for 5-10 min (Table 1) (35)(36)(37). The participants were advised to wear knee straps and modify activities (38).…”
Section: Conventional Physical Therapymentioning
confidence: 99%
“…Massage therapy has therapeutic advantages, which has been proposed as a modality with several benefits. Numerous systematic reviews and more than 300 clinical studies have examined massage therapy's effectiveness for various conditions 14 . For example, systematic studies have indicated that myofascial release massage helps treat plantar fasciitis and that massage therapy using soft tissues may effectively treat shoulder discomfort.…”
Section: Introductionmentioning
confidence: 99%